2019
DOI: 10.1103/physrevd.100.101501
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamical hairs of the four-dimensional Taub-Newman-Unti-Tamburino spacetimes

Abstract: It is demonstrated that the generic four-dimensional Taub-Newman-Unti-Tamburino (Taub-NUT) spacetimes can be perfectly described in terms of three or four different kinds of thermodynamic hairs: the Komar mass (M ¼ m), the "angular momentum" (J n ¼ mn), the gravitomagnetic charge (N ¼ n), and/or the dual (magnetic) mass (M ¼ n). In other words, the NUT charge is a thermodynamic multihair which means that it simultaneously has both rotation-like and electromagnetic charge-like characteristics; this is in sharp … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 56 publications
3
53
0
Order By: Relevance
“…The thermodynamics of black holes with NUT parameter have been investigated extensively [42][43][44][45][46]. The first law of thermodynamics for the Kerr-Taub-NUT black hole is [43]…”
Section: Kerr-taub-nut Black Hole and Its Thermodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermodynamics of black holes with NUT parameter have been investigated extensively [42][43][44][45][46]. The first law of thermodynamics for the Kerr-Taub-NUT black hole is [43]…”
Section: Kerr-taub-nut Black Hole and Its Thermodynamicsmentioning
confidence: 99%
“…Recently, black holes with NUT charge have attracted some interesting researches, such as gravitational lensing [40], thermodynamics and phase transition [41][42][43][44][45][46], strong cosmic censorship conjecture [47] and weak cosmic censorship conjecture [48]. In this paper, we investigate the validity of the weak cosmic censorship conjecture for Kerr-Taub-NUT black holes by considering scattering of a test massive scalar field and injection of a test particle, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Another direction towards the interpretation of the NUT space-time comes from the analysis of its thermodynamic properties. In [36] it was shown that if the NUT parameter is interpreted as possessing simultaneously rotational and electromagnetic features then the thermodynamic equivalent of Bekenstein-Smarr formula follows naturally. Another famous solution of the above class is the ZV space-time describing the gravitational field outside a static deformed object [10,11].…”
Section: Stationary Zipoy-voorhees Metricmentioning
confidence: 99%
“…a stationary solution that has been thoroughly investigated, is the so-called Newman-Unti-Tamburino (NUT) space-time [34], which, due to its peculiar properties, was at some point referred to as a 'counterexample to everything' [35]. However, arguments exist in support to the fact that the NUT solution could posses some physical validity and the NUT parameter could in fact be related to angular momentum (see for example [36]). Similarly to Kerr, the NUT space-time is fully characterized by two parameters, one related to the mass of the source, and the other, the so-called NUT parameter, related to the gravitomagnetic charge of the source.…”
Section: Introductionmentioning
confidence: 99%
“…Although our treatment and the one in [21] have the same general idea of introducing a pair of thermodynamical variables N − Φ N , which is a natural consequence of having independent r 0 and n, the two approaches are different in their mass and their first law looks different as we will see below. While preparing this work we found the appearance of another related paper [39] which introduces again the same general idea of adding extra thermodynamic pairs, but this time it adds two new charges n and m n to study the thermodynamics of Lorentzian Taub-Bolt and NUT solutions with spherical horizons. Although this work studies a different class of Taub-Bolt/NUT solutions with different signature which includes electrically charged Taub-Bolt solutions it did not include the dyonic solution we studied here.…”
Section: Introductionmentioning
confidence: 99%